EstDZ3: A New Esterolytic Enzyme Exhibiting Remarkable Thermostability - Zarafeta, Dimitra; Szabo, Zalan; Moschidi, Danai; Phan, Hien; Chrysina, Evangelia D.; Peng, Xu; Ingham, Colin J.; Kolisis, Fragiskos N.; Skretas, Georgios (Frontiers in Microbiology, 2016)
Lipolytic enzymes that retain high levels of catalytic activity when exposed to a variety of denaturing conditions are of high importance for a number of biotechnological applications. In this study, we aimed to identify new lipolytic enzymes, which are highly resistant to prolonged exposure to elevated temperatures. To achieve this, we searched for genes encoding for such proteins in the genomes of a microbial consortium residing in a hot spring located in China. After performing functional genomic screening on a bacterium of the genus Dictyoglomus, which was isolated from this hot spring following in situ enrichment, we identified a new esterolytic enzyme, termed EstDZ3. Detailed biochemical characterization of the recombinant enzyme, revealed that it constitutes a slightly alkalophilic and highly active esterase against esters of fatty acids with short to medium chain lengths. Importantly, EstDZ3 exhibits remarkable thermostability, as it retains high levels of catalytic activity after exposure to temperatures as high as 95°C for several hours. Furthermore, it exhibits very good stability against exposure to high concentrations of a variety of organic solvents. Interestingly, EstDZ3 was found to have very little similarity to previously characterized esterolytic enzymes. Computational modeling of the three-dimensional structure of this new enzyme predicted that it exhibits a typical α/β hydrolase fold that seems to include a “subdomain insertion”, which is similar to the one present in its closest homolog of known function and structure, the cinnamoyl esterase Lj0536 from Lactobacillus johnsonii. As it was found in the case of Lj0536, this structural feature is expected to be an important determinant of the catalytic properties of EstDZ3. The high levels of esterolytic activity of EstDZ3, combined with its remarkable thermostability and good stability against a range of organic solvents and other denaturing agents, render this new enzyme a candidate biocatalyst for high-temperature biotechnological applications.